Analisis Pengaruh Variabel Makroekonomi Terhadap Inflasi Di Indonesia - Dina Apriliani (Ekopem: Jurnal Ekonomi Pembangunan, 2022)
Inflation is a process of increasing prices in general that occurs continuously in an economy. This study aims to see the effect of BI interest rates, exchange rates and e-money on inflation in Indonesia for the 2018-2021 period. The data used in this study is secondary data in the type of 4-year time series data starting from January 2018 to December 2021. By using the multiple regression analysis method. The results of the study show that interest rates have a positive and significant effect on inflation in Indonesia. The exchange rate has a negative and insignificant effect on inflation in Indonesia. E-money has a negative and significant effect on inflation in Indonesia. Meanwhile, simultaneously interest rates, exchange rates and e-money together have a significant effect on inflation in Indonesia.